Trade liberalization in the presence of domestic regulations: public policies applied to EU and U.S. wine markets. Issue 18 (15th April 2018) - Rickard, Bradley J.; Gergaud, Olivier; Ho, Shuay-Tsyr; Livat, Florine
ABSTRACT: Wine is the highest valued product in the agricultural, food, and beverage sector traded between the United States and the European Union (EU) and wine faces a range of tariffs that are differentiated by country and product category. In addition, the production of wine grapes is heavily regulated within the EU and there are complicated state-level policies in the United States designed to limit the retail availability of wine. There continues to be economic and political pressure for reform to the tariffs between the United States and the EU, and to the domestic regulations in each region. We carefully develop parameters to characterize the effects of tariffs and domestic regulations that affect production and consumption of wine in the two regions. Simulation results show that reductions in tariffs would have relatively small effects in EU and U.S. wine markets, whereas reductions in EU domestic policies that affect wine grape production would have much larger trade and welfare implications.